First records of Miracinae (Hymenoptera: Braconidae) from Borneo with description of two new species - Liu, Zhen; Polaszek, Andrew (European Journal of Taxonomy, 2024)
The braconid subfamily Miracinae is recorded for the first time from Borneo. Two new species are described: Rugosimirax obsolescens sp. nov. and Rugosimirax bimacula sp. nov. based on specimens in the Natural History Museum, UK. The relationships of Miracinae genera are discussed.